IMPLEMENTASI KEBIJAKAN PENGANGKATAN APARATUR SIPIL NEGARA DALAM JABATAN STRUKTURAL DI KABUPATEN INDRAGIRI HILIR PROVINSI RIAU - jurnalmap map; Herawati ÔÇÄ; Sri Mulyani; Hadi Susanto (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2021)
This study aims to describe the implementation of the policy of appointing state civil servants in structural positions and the factors that influence them in Indragiri Hilir Regency. This research uses descriptive qualitative research and data collection with in-depth interviews. The process of implementing ASN appointment in Indragiri Hilir Regency there are 5 stages including planning, announcement, registration, selection and appointment. Planning is carried out based on the proposed workforce needs and the slack of officials in the region which are forwarded to each agency. The announcement phase was carried out by the Baperjakat Team after it was discovered that the SKPD needed employees and had been scheduled beforehand. The registration and selection stage for the appointment of the State Civil Apparatus in Indragiri Hilir Regency is the core stage in the appointment process. The final stage in the process of appointing a State Civil Apparatus in a position in Indragiri Hilir Regency is the appointment stage. This stage was carried out after the ASN candidate had carried out the examination and was declared eligible to become a State Civil Apparatus.Keywords: appointment, state civil apparatus